Leading Through Dualism: Servant Leadership, Organizational Citizenship Behavior, and Employee Performance in an Indonesian Rural Cooperative - Yurmanius Waruwu; Endang Suswati; Sugeng Mulyono; Gunadi (Global Research Collaboration, 2026)
Cooperatives play a significant role in supporting community-based economic development and expanding access to financial services for local communities in Indonesia. However, governance challenges, such as leadership dualism, can generate organizational instability that potentially undermines employee performance. This study aims to examine the relationship between Servant Leadership and Employee Performance and to test the mediating role of Organizational Citizenship Behavior (OCB) in a cooperative experiencing leadership dualism. A quantitative approach with an explanatory design was used. The population and sample consisted of 117 permanent employees of the Nias Rural Savings and Financing Cooperative (KSP3 Nias), selected through total sampling method. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that Servant Leadership is positively and significantly associated with both OCB (β = 0.764, p < 0.001) and Employee Performance (β = 0.345, p = 0.002). Furthermore, OCB partially mediated the relationship between Servant Leadership and Employee Performance (indirect effect = 0.391, p < 0.001), with Servant Leadership and OCB jointly explaining 71.2% of the variance in Employee Performance (R² = 0.712). These results suggest that a servant-oriented leadership approach is associated with higher levels of voluntary extra-role behavior among employees, which, in turn, appears to function as a stabilizing factor for organizational performance, even under conditions of structural conflict.